Revisiting Temporal Evolution of Cu-Rich Precipitates in Fe–Cu Alloy: Correlative Small Angle Neutron Scattering and Atom-Probe Tomography Studies. (August 2019) - Ahlawat, Sarita; Sarkar, Sudip Kumar; Sen, Debasis; Biswas, Aniruddha
Abstract: Binary Fe–Cu alloys are effective prototypes for investigating radiation-induced formation and growth of nanometric Cu-rich precipitates (CRPs) in nuclear reactor pressure vessels. In this report, the temporal evolution of CRPs during thermal aging of Fe–Cu binary alloys has been investigated by using complementary techniques such as atom probe tomography (APT) and small-angle neutron scattering (SANS). We report a detailed quantitative evolution of a rarely observed morphological transformation of Cu precipitates from spherical to ellipsoid with a significant change (approximately two times) in aspect ratio, an effect known to be associated with the 9R-3R structural transition of the precipitates. It is demonstrated through APT that the precipitates remain spherical up to 8 h, however, they subsequently convert to oblate ellipsoid upon further aging. SANS analysis also detected signs of this morphological transition in reciprocal space. Furthermore, SANS quantifies evolution of the precipitates and corroborates well with the APT results. Interestingly, the power-law exponent of the temporal evolution for mean size and number density agree reasonably well with the Lifshitz–Slyozov–Wagner model, in spite of the complex morphological evolution of the precipitates.